The impact of bio-stimulators on zucchini plants under pre-sowing seed treatment - Pysarenko, V.; Pischalenko, M.; Chaika, T.; Lohvynenko, V.; Krupska, N.; Koroleviat, Y.; Kirieiev, Y. (Scientific Progress & Innovations, 2023)
Nowadays, there are a considerable number of technological innovations in the field of agriculture, aimed at increasing stress-resistance, yield capacity, and the quality of grown products by decreasing the application of chemical means. The use of bio-stimulators, such as plant extracts or micro-organisms is a promising direction, which improves plant growth and effective use of the available soil resources, reclaims its fertility, decreases industry-related load, etc. The purpose of the article is to study the application of bio-stimulators for pre-sowing seed treatment and their impact on zucchini plants. Pre-sowing zucchini seeds treatment with bio-stimulator is an important reserve for raising the yield and improving the product quality, as well as the plants’ growth and health by stimulating natural processes. Taking into account that zucchini has a high yield potential per unit of area during a short vegetation period, it is expedient to improve the farming method of its cultivation. For example, it is advisable to use silica combinations, Trichoderma or rhizo-bacteria, and plant extracts, which stimulate the plants’ growth. The application of P. putida S1Pf1 and Pseudomonas spp. 5Vm1К bacteria strains results in increasing the duration of blooming, the number of flowers and fruits. It has been determined that zucchini seeds treatment with Stimulate® and chitosan assists in seed germination and, at the combination of Eucalyptus camaldulensis leaf extract + K2SiO3 + Trichoderma viride, it is possible to get the highest yield of fruits. It has been found that as a result of zucchini seed treatment with Emistim C and Vermisol bio-stimulators the germinating energy and field germination increases, the yield grows and product quality improves, abiotic stress and phyto-toxic effect of pesticides decreases, the amount of residual pesticides diminishes, etc. Thus, bio-stimulators play a vital role in the nutrient cycle, the control of abiotic stress, and other important processes in zucchini plants, which enables to consider them promising agricultural practices.